Nerve conductive study in women with carpel tunnel syndrome in Tikrit city - T. Ismael, Umer (Tikrit Journal of Pharmaceutical Sciences, 2023)
Carpal tunnel syndrome (CTS) is one of the most common upper limb compression neuropathies. CTS account for approximately 90% of all entrapment neuropathies. An estimated one million adults from the United States (annually) have CTS requiring medical treatment. The aim of the study is to investigate to compare the normal values of median nerve of normal healthy women (distal latency, amplitude & conduction velocity) with the same values of median nerve in women with carpel tunnel syndrome. The study was conducted as a case series study for Iraqi volunteers and patients attended to rheumatology department - neurophysiology unit at Tikrit teaching hospital (TTH) at the period from the 1st of December 2010 to the 1st of August 2011. Forty healthy female subjects with a mean age of (40.315 ± 10.324 years) to compare with the CTS female patients. Thirty eight female patients with mean age group of (40.55 ± 10.230 years) with CTS affect them in right hand diagnosed by rheumatologist and neurologist then referred to nerve conductive study (NCS) and EMG unit at TTH. The NCS was done by using NIHON KOHDEN / Neuropack S1 EMG / EP Measuring System MEB-9400 MODEL 2009. There are no significance differences between control subjects & CTS patients regarding age, body mass index. Also, there are no significance difference between normal control subjects & CTS patients in regard to upper limb length, arm circumference, index finger length (IFL), index finger circumference and wrist circumference. In regard to motor activity of median nerve, there is significance increase in distal latency time of median nerve of CTS patients (5.632 ± 1.791 msec) on compare to normal control subjects (3.540 ± 0.622 msec). Also, the amplitude of action potential of motor activity of median nerve is higher in control subjects (9.217 ± 0.509 mv) in compare to CTS patients motor activity of amplitude of (6.530 ± 1.937 mv). The difference between median nerve motor amplitude is significance at ( p<0.01) between patients and controls. Moreover the conduction velocity in CTS patients of median motor (58.354 ± 1.789 m/sec) is significance lower (p<0.01) in compare to motor conduction values of median nerve in normal control subjects (53.744 ± 4.232 m/sec). However, in regard to sensory activity of median nerve in right hand of both normal control subjects and CTS patients. The latency period in CTS patients is delayed (3.414 ± 1.606 msec) in compare to normal subjects (2.761 ± 0.344 msec). While, the amplitude of action potential of the sensory activity of median nerve is significantly lower (p< 0.01) in compare to normal subjects. Also, the conduction velocity of sensory activity of median nerve of CTS patients is significantly lower (38.357 ± 4.357 m/sec) on compare to conduction velocity of sensory activity of median nerve of normal subjects (48.236 ± 2.545 m/sec). The present study concludes that: The present study showed abnormal values NCS of median nerve at CTS patients as compare to normal healthy women of same age. The present study recommend that;- Using median nerve ultrasonography as diagnostic tools to confirm or exclude CTS & minimize false positive results.